'Space is blue and birds fly through it'. (13th July 2018) - Rovelli, Carlo
Abstract : Quantum mechanics is not about 'quantum states': it is about values of physical variables. I give a short fresh presentation and update on the relational perspective on the theory, and a comment on its philosophical implications. This article is part of a discussion meeting issue 'Foundations of quantum mechanics and their impact on contemporary society'.